The Economic Consequences of Internal Displacement in Zimbabwe - Mandishekwa, Robson (Midlands State University, 2022)
The Economic Consequences of Internal Displacement in Zimbabwe Background: Internal displacement occupies a central place among population displacements especially in Africa where Internally Displaced Persons (IDPs) have outnumbered refugees, hence, the term Africa’s new dilemma. Africa has also become a host to two-thirds of the world's IDPs. With the increasing demand for minerals, mining-induced displacement has taken a centre stage among development projects. Despite the increasing trend in the number of IDPs, few studies have focused particularly on economic consequences of mining-induced internal displacement, yet mining-induced displacements cannot be ruled out given the ongoing explorations and increasing demand for minerals as a result of population growth. Furthermore, there is scant literature on economic activities and satisfaction with life among displacees. IDPs have, therefore, remained the forgotten group, both in literature and in policy issues. To contribute to the literature, the thesis explored the economic consequences of mining-induced displacement, determinants of the choice of economic activities and determinants of satisfaction with life among IDPs in Arda Transau, Zimbabwe.